Post-Divorced Transitions: Mental Health and Suicide Ideation Among Canadian Fathers - Kenedy, Robert A. (International Journal for Family Research and Policy, 2015)
Do fathers matter after separation or divorce? The data based on this Canadian study of 208 fathers, mothers, grandparents, and adult children indicates that children, mothers, and especially fathers seem unimportant after separation and divorce. The initial purpose of this study was to examine the connection between the family law system and the impact this system and the court have on separated and divorced parents as well as their reasons for activism. One of the unexpected findings that emerged was how frequently separated and divorced fathers reported personal mental health issues and suicide ideation. These issues were often associated with being dismissed by the courts as disposable “social” post-separation/divorced parents. The main problem is that these parents and activists are disregarded due to the negative perceptions by the family law courts of both the shared parenting movement and fathers. This perceived negation has impacted fathers’ mental health issues and suicide ideation as well as their activism in the shared parenting movement.